Technology-aided programs for post-coma patients emerged from or in a minimally conscious state - Lancioni, Giulio E.; Singh, Nirbhay N.; O’Reilly, Mark F.; Sigafoos, Jeff; Olivetti Belardinelli, Marta; Buonocunto, Francesca; D’Amico, Fiora; Navarro, Jorge; Lanzilotti, Crocifissa; Ferlisi, Gabriele; Denitto, Floriana (Frontiers in Human Neuroscience, 2014)
Post-coma persons in a minimally conscious state (MCS) or emerged/emerging from such state (E-MCS), who are affected by extensive motor impairment and lack of speech, may develop an active role and interact with their environment with the help of technology-aided intervention programs. Although a number of studies have been conducted in this area during the last few years, new evidence about the efficacy of those programs is warranted. These three studies were an effort in that direction. Study I assessed a technology-aided program to enable six MCS participants to access preferred environmental stimulation independently. Studies II and III assessed technology-aided programs to enable six E-MCS participants to make choices. In Study II, three of those participants were led to choose among leisure and social stimuli, and caregiver interventions automatically presented to them. In Study III, the remaining three participants were led to choose (a) among general stimulus/intervention options (e.g., songs, video-recordings of family members, and caregiver interventions) and then (b) among variants of those options. The results of all three studies were largely positive with substantial increases of independent stimulation access for the participants of Study I and independent choice behavior for the participants of Studies II and III. The results were analyzed in relation to previous data and in terms of their implications for daily contexts working with MCS and E-MCS persons affected by multiple disabilities.